Global equity in access to healthcare information: a call to action (Journal of EAHIL, 2023)
We invite EAHIL colleagues to take 5 minutes to complete the survey on Universal access to reliable healthcare information(available in multiple languages), and to promote it within their organisations. Complete the survey: www.hifa.org/survey2023 [available until 30 September] Further information: https://www.hifa.org/projects/hifa-who-global-consultation-2023  - this includes a communication brief and promotional materials